Influence of Product Quality, Price, Promotion and Place Regarding the Decision to Purchase from a Coffee House, Batam - Rahmatullah, Muhammad Rizky; Hidayat, Rizki (Universitas Batam, 2022)
Marketing is an important factor in the development of the business. Marketing must be continually upgraded and refurbished, of course it’s not be separated from the needs and desires of consumers. So dynamic or uncertainty in knowing the consumer desires, so in this case required every business must always be able to make changes such as product quality, price, promotion and place on purchase decisions Dari Rumah Coffee, Batam. The purpose of this study is to analyze the effect of product quality, price, promotion and place on purchase decisions Dari Rumah Coffee, Batam. The method used is multiple linear regression analysis. The study population of 216 consumers and samples used by 140 respondents. Research shows that the Product Quality, Price and Place partially significant effect on the Product Buying Decision. While Price partially not significant effect on the Product Buying Decision. Simultaneously Product Quality, Price, Promotion and Place have significant effect on the Product Buying Decision.